The Complete Plays of Gilbert and Sullivan - Gilber, W.S. (New York Random House Inc, 1936)
This volume contains the complete, authorized text of the foutteen operas for which Gilbelr wrote the librettos and Sullivan the music, with the original illustratios by W.S. Gilbert.
Keywords: Literature